A Review Paper On Effects Of Slurry Concentration on Wear of Turbine Steels - Paras Khullar, Manpreet Singh (International Journal of Advanced Science and Technology, 2020)
This paper is a study and comparison of effects of slurry concentration on the wear of hydro turbine steels or a similar work performed by different authors. Various base materials used as hydro turbine steels for different working parameters. Also in some cases, a number of coatings have also been done on the base materials. The work pieces have been checked on different testers and for different parameters. At the end a conclusion was derived regarding effect of slurry concentration on slurry erosion of turbine steels.